2021
DOI: 10.1007/s00431-021-04222-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent seroprevalence of SARS-CoV-2 antibodies in school-aged children from areas with low and high community transmission

Abstract: It is not yet clear to what extent SARS-CoV-2 infection rates in children reflect community transmission, nor whether infection rates differ between primary schoolchildren and young teenagers. A cross-sectional serosurvey compared the SARS-CoV2 attack-rate in a sample of 362 children recruited from September 21 to October 6, 2020, in primary (ages 6–12) or lower secondary school (ages 12–15) in a municipality with low community transmission (Pelt) to a municipality with high community transmission (Alken) in B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
2
26
2
1
Order By: Relevance
“…For example, studies conducted in French 9 and British primary schools and French day cares 10 suggested little evidence of transmission from children to their peers or teachers, and a large Swiss cohort 11 found minimal clustering of seropositive cases within classes and schools, despite a clear increase in seroprevalence in children over a 5-month period of very high transmission. Determinants of SARS-CoV-2 seropositivity among children have included contact with a confirmed COVID-19 case, 10 , 12 health care workers in the household, 12 belonging to a minority racial or ethnic group, and geographical area. 11 One year into the pandemic, little is known regarding the seroprevalence of SARS-CoV-2 infection and its determinants among children and adolescents in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies conducted in French 9 and British primary schools and French day cares 10 suggested little evidence of transmission from children to their peers or teachers, and a large Swiss cohort 11 found minimal clustering of seropositive cases within classes and schools, despite a clear increase in seroprevalence in children over a 5-month period of very high transmission. Determinants of SARS-CoV-2 seropositivity among children have included contact with a confirmed COVID-19 case, 10 , 12 health care workers in the household, 12 belonging to a minority racial or ethnic group, and geographical area. 11 One year into the pandemic, little is known regarding the seroprevalence of SARS-CoV-2 infection and its determinants among children and adolescents in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the densely populated and well-connected region of Flanders, SARS-CoV-2 infection rates show a local distribution (34), dependent on heterogeneous mixing patterns and subject to different policies (35,36). Research shows that transmission in schools depends on the level of community transmission (37,38). School cases show a high correlation with the evolution of community cases in the general population in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted throughout 2021 brought further understanding to a spectrum of clinical symptoms and patterns of spread of the COVID-19 in children [ 47 - 70 ]. A study in Belgium found anti-SARS-CoV-2 antibodies in 4.4% of children in the low transmission region and 14.4% of children in the high transmission region.…”
Section: Early Research On the Symptoms And Spreading Of The Sars-cov-2 Among Children And Young Peoplementioning
confidence: 99%
“…A higher risk of seropositivity was associated with a contact with a confirmed case (RR = 2.9), participation in extracurricular activities (RR = 5.6), or a caregiver health care worker who had contact with COVID-19 patients (RR = 2.2). The study showed that, when SARS-CoV2 circulation in the community is high, this will be reflected in the pediatric population with similar infection rates [ 47 ]. A clear association was established between the duration of the COVID-19 symptoms in children and the generated IgG units [ 48 ].…”
Section: Early Research On the Symptoms And Spreading Of The Sars-cov-2 Among Children And Young Peoplementioning
confidence: 99%